Heart Rate Variability and Cognitive Function: A Systematic Review - Forte, Giuseppe; Favieri, Francesca; Casagrande, Maria (Frontiers in Neuroscience, 2019)
Background Autonomic dysfunctions may precede the development of cognitive impairment, but the connection between these dimensions is unclear. This systematic review aims to analyse the relationship between heart rate variability and cognitive functions. Methods The review process was conducted according to the PRISMA-Statement. Restrictions were made, selecting the studies in English and published in peer-review journals, including at least one cognitive measure and presenting the measurement of HRV. Studies that included participants with medical conditions, dementia, psychiatric disorders, strokes, and traumatic brain injury were excluded. Twenty studies were selected, with a total of 19,431 participants. The results were divided into different cognitive domains determined a priori: global cognitive functioning, attention, processing speed, executive functions, memory, language and visuospatial skills. Results Both increased sympathetic activity and decreased parasympathetic activity seem to be associated with a worse performance in the cognitive domains considered, in the absence of dementia and severe cardiovascular diseases or other medical and psychiatric diseases. Conclusions The results highlight the influence of the autonomic nervous system in cognitive functioning. However, the marked interest facing towards a specific domain, i.e., the executive functions, and the relatively small number of the studies on this topic do not allow understanding better this relationship. Despite these limits, HRV could be considered a promising early biomarker of cognitive impairment in populations without dementia or stroke. This index should be evaluated within a preventative perspective to minimise the risk of developing cognitive impairment.